Effect of sensory retraining program on latency, amplitude and conduction velocity of sensory nerves of lower limb in type 2 diabetic peripheral neuropathy - Maruboyina, Sowjanya; Attry, Sanjeev; Kumari B. , Kusuma; Reddy K. , Eswar; Perakam, Sravanthi (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. India is known as the world’s diabetes capital. Diabetic neuropathy is the most common complication of diabetes, and if not managed properly, leads to diabetic foot complications like ulcers and amputations. Physiotherapy interventions addressing these complications are very limited. Hence, this study was performed to access to what extent a sensory retraining program affects the latency, amplitude, and conduction velocity of the sural nerve in lower limbs. The study aims to improve the nerve conduction velocity of the sural nerve in diabetic neuropathy with a sensory retraining program. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. One-hundred individuals who met the inclusion criteria were randomly allocated into 2 groups. The control group had received routine medical care. The experimental group individuals were managed with a sensory retraining program 5 days a week for 16 weeks. Latency, amplitude, and conduction velocity values were recorded before and after the study. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Results conclude that the sensory retraining program is effective in decreasing the latency and improving conduction velocity. It did not have any effect on the amplitude. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Hence, we conclude that a sensory retraining program can be incorporated into routine physical therapy intervention in subjects with diabetic peripheral neuropathy.